AMX – the highly automated macromolecular crystallography (17‐ID‐1) beamline at the NSLS‐II. (21st October 2022) - Schneider, Dieter K.; Soares, Alexei S.; Lazo, Edwin O.; Kreitler, Dale F.; Qian, Kun; Fuchs, Martin R.; Bhogadi, Dileep K.; Antonelli, Steve; Myers, Stuart S.; Martins, Bruno S.; Skinner, John M.; Aishima, Jun; et al.
Abstract : AMX (17‐ID‐1) is the highly automated macromolecular crystallography beamline at the NSLS‐II. Photon delivery system, beamline instrumentation, high‐performance computing environment and suites of applications are described for beamline scientists and users. AMX's primary mission is to support routine structure determination from the most challenging projects. Abstract : The highly automated macromolecular crystallography beamline AMX/17‐ID‐1 is an undulator‐based high‐intensity (>5 × 10 12  photons s −1 ), micro‐focus (7 µm × 5 µm), low‐divergence (1 mrad × 0.35 mrad) energy‐tunable (5–18 keV) beamline at the NSLS‐II, Brookhaven National Laboratory, Upton, NY, USA. It is one of the three life science beamlines constructed by the NIH under the ABBIX project and it shares sector 17‐ID with the FMX beamline, the frontier micro‐focus macromolecular crystallography beamline. AMX saw first light in March 2016 and started general user operation in February 2017. At AMX, emphasis has been placed on high throughput, high capacity, and automation to enable data collection from the most challenging projects using an intense micro‐focus beam. Here, the current state and capabilities of the beamline are reported, and the different macromolecular crystallography experiments that are routinely performed at AMX/17‐ID‐1 as well as some plans for the near future are presented.